PENGARUH KEMAMPUAN DAN MOTIVASI TERHADAP KINERJA UNIT PENGELOLAAN DANA SIMPAN PINJAM PEREMPUAN - La Ode Kimon; Weka Widayati; La Rianda (Jurnal Sosio Agribisnis, 2017)
This study aims to determine the effect of ability and motivation on the performance of the savings and loan fund management unit for women. The study was conducted in Muna Regency, Southeast Sulawesi Province with a sample of 51 administrators of a savings and loan fund management unit for women in the Rural Independent Community Empowerment Program. Determination of sample using census method. Data analysis was carried out descriptively and using SEM (Structural Equation Modeling). The results of the study showed that the score of the administrator’s capacity of the savings and loan fund management unit for women was 65 percent, while the motivation score was 75 percent, and the performance score was 82 percent. The results of SEM (Structural Equation Modeling) analysis show that the performance of the management unit of the savings and loan fund for women is influenced by ability with a coefficient value of 0.49 formed by education and knowledge with a coefficient of 0.75 and skills of 0.89. Motivation affects performance with a coefficient of 0.46 formed by fisilogis with a coefficient of 0.52, security of 0.66, possession and ownership of 0.67, appreciation of 0.58, self-actualization needs of 0.53.Keywords: abilities, motivations, performance, woman